Characterisation of flavour compounds formed by gamma-irradiation of polypropylene - Tyapkova, Oxana; Czerny, Michael; Büttner, Andrea (Polymer Degradation and Stability, 2009)
Sterilisation of plastic packaging materials for food, pharmaceutical or cosmetic products with 60Co γ-irradiation in the presence of oxygen can result in the formation of volatile substances. These may subsequently induce off-odours in these materials that might be regarded as negative by the consumers. Trace volatiles and odorous substances of polypropylene, irradiated with 60Co γ rays at 10 and 20 kGy, respectively, were collected and analysed by gas chromatography-olfactometry (GC-O), GC-MS and GC-GC-MS. The methodology was successfully applied for identification of 29 characteristic odorants in a non-irradiated control sample and 38 odorants in γ-irradiated polypropylene samples. Selected odour-active compounds were quantified using GC-GC-MS in combination with stable isotope dilution assays. The quantitative data mirrors the compositional changes in volatile odorous substances from polypropylene during treatment with ionising γ rays in a 60Co-irradiation plant. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.charac
Keywords: γ-Irradiation; Aroma extract dilution analysis (AEDA); Gas chromatography-olfactometry (GC-O); Polypropylene (PP); Radiolysis products